Water for a city (Physical resources and environment ;, 1986)
Summary: Investigates the water supply for the city of Nottingham, UK. THe programme explores groundwater supply; the Derwent and Ladybower reservoirs and dams; the Carsington Reservoir and dam; and extraction from the River Derwent.